The Reality of Using Virtual Laboratories at the University of Misan from Teachers' Perspective - Shaimaa Jasim Mohammed ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2021)
This study aims at finding The Reality of Using Virtual Laboratories at the University of Misan from Teachers' Perspective, The researcher followed the descriptive research method, and the research sample consisted of teachers who study practical side in Realistic laboratories at the University of Misan. The number is (50) teachers, and to reach the goal of the research, the researcher prepared a research labs represented by the questionnaire, which consisted of (26) paragraphs organized in three axes,  and after verifying the validity and stability of the questionnaire, it was applied to the sample, data was collected, and it was treated statistically. The results showed the extent of the possibility of using virtual laboratories, highlighting the importance and identifying obstacles to their use, and based on the results, the researcher made a number of recommendations, including holding training courses for teachers and introducing them to how to use virtual laboratories, and providing a free internet with high efficiency, establishing virtual laboratories and providing them with all supplies, She suggested conducting similar research to find out the importance of using virtual laboratories from the point of view of students at the University of Misan and  knowing the reality of the use of virtual laboratories in other universities, and conducting empirical research to investigate the effect of using virtual laboratories on the achievement of students in different academic stages and subjects.